"Fête de la Soupe": rural identity, self-representation, and the(re)-making of the village in France. Issue 3 (13th August 2018) - Ducros, Hélène B.
Abstract : Purpose: The purpose of this paper is to explore a grassroot festival in rural France organized around the concept of soup. The annual fête de la soupe held in a village in Auvergne provides a small-scale example of the ways in which space, time and festivalization interact in placemaking. Design/methodology/approach: Ethnographic research highlights the motivations and experiences of the organizers and volunteer-participants, as well as some of the organizational challenges. Findings: Revealing that the profit motive and economic outcomes are not dominant, this paper shows instead that the fête constitutes a space of relation-building between place and people, between people themselves and an introspective moment over the past and future of place as "rural". While preserving rurality symbolized and mediated by the exchange of soup as the ultimate peasant dish, the festival is also an opportunity for villagers to revitalize the rural and showcase it as a place of creativity. Originality/value: The study addresses the experience of volunteers and organizers in festivals, uses qualitative methods to do so and focuses on festivals in the rural setting, filling three gaps identified by others in the literature.